Characterizing scintillator detector response for correlated fission experiments with MCNP and associated packages - Andrews, M.T.; Rising, M.E.; Meierbachtol, K.; Talou, P.; Sood, A.; Bates, C.R.; McKigney, E.A.; Solomon, C.J. (Radiation physics and chemistry (Oxford, England : 1993), 2019)
When multiple neutrons are emitted in a fission event they are correlated in both energy and their relative angle, which may impact the design of safeguards equipment and other instrumentation for non-proliferation applications. The most recent release of MCNP6.2 contains the capability to simulate correlated fission neutrons using the event generators CGMF and FREYA. These radiation transport simulations will be post-processed by the detector response code, DRiFT, and compared directly to correlated fission measurements. DRiFT has been previously compared to single detector measurements, its capabilities have been recently expanded with correlated fission simulations in mind. This paper details updates to DRiFT specific to correlated fission measurements, including tracking source particle energy of all detector events (and non-events), expanded output formats, and digitizer waveform generation. •MCNP6.2 includes the correlated fission event generators CGMF and FREYA.•MCNP and associated packages DRiFT and MCNPTools are used to simulate scintillator measurements of correlated fission.•DRiFT detector response capabilities have been expanded for correlated fission simulations.•New capabilities in DRiFT include tracking source particle information, expanded output formats and digitizer waveform generation.